2021
DOI: 10.1038/s41598-021-89993-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA detection of an invasive ant species (Linepithema humile) from soil samples

Abstract: Alien ant species (Formicidae, Hymenoptera) cause serious damage worldwide. Early detection of invasion and rapid management are significant for controlling these species. However, these attempts are sometimes hindered by the need for direct detection techniques, such as capture, visual observation, or morphological identification. In this study, we demonstrated that environmental DNA (eDNA) analysis can be used as a monitoring tool for alien ants using Linepithema humile (Argentine ant), one of the most invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In soil samples, eDNA detectability from areas of ant transit was lower than that of ant nesting areas. A recent study on Argentine ants eDNA also found the highest eDNA concentration in soil from nest entrances, as opposed to surface soil samples from an infestation area and found no relationship between eDNA concentration and distance from nests or trails (Yasashimoto et al, 2021). The authors argued that Argentine ants may move nests frequently, and therefore strong relationships between eDNA concentration and distance from a nest were not expected (Yasashimoto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In soil samples, eDNA detectability from areas of ant transit was lower than that of ant nesting areas. A recent study on Argentine ants eDNA also found the highest eDNA concentration in soil from nest entrances, as opposed to surface soil samples from an infestation area and found no relationship between eDNA concentration and distance from nests or trails (Yasashimoto et al, 2021). The authors argued that Argentine ants may move nests frequently, and therefore strong relationships between eDNA concentration and distance from a nest were not expected (Yasashimoto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…obs .). Their variable nesting and foraging behaviour make choosing appropriate sites from which to sample soil for eDNA more challenging than it may be for other species such as Argentine ants (Yasashimoto et al, 2021). The first recorded infestation in mainland Australia was in the Northern Territory in the early 1990s (Majer, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, LAMP assays have also been developed to amplify DNA from microscopic pathogens and parasites in water samples and other fluid matrices (29)(30)(31)(32), with one example of LAMP eDNA detection for a marine mollusc in ex-situ conditions (33). Between both molecular methods, qPCR has so far been used to successfully amplify insect eDNA from soil (17) and fecal (34) environmental matrices while LAMP-based assays had until this study not been tested to detect insect DNA in any environmental matrix, but failed to detect T. granarium eDNA in dust samples. Non-detection may be associated to the mechanism used in LAMP to amplify DNA, in which the six primers bind laterally to distinct sites using stranddisplacement Bst DNA polymerase to amplify a single fragment of DNA (35).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a need to test and develop molecular methods that complement the needs of biosecurity officers during biosecurity responses. Environmental DNA (eDNA)-based methods have been shown to be cost-effective reliable methods to inform users on the presence of target species in surveillance applications (15), with studies showing how eDNA-based detection using soil and airborne dust samples can provide valuable data on species presence and diversity (16)(17)(18). When used with portable, pointof-care technologies, eDNA-based detection can offer sensitive detection tools to support management of biosecurity risks (19), ADDIN EN.CITE (16)(17)(18)but no studies have so far tested suitable extraction methods of dust samples and the utility of portable technologies during biosecurity applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have utilized these approaches to detect target organisms, estimate species biomass from samples, and development indices for assessing the disturbance in aquatic environments (Graham et al, 2019 ; Knudsen et al, 2019 ; Kodama et al, 2022 ; Laramie et al, 2015 ; Scriver et al, 2015 ). However, eDNA‐based biomonitoring has not been as widely used for the terrestrial environment in the same way (Katz et al, 2021 ; Saitoh et al, 2016 ; Yasashimoto et al, 2021 ). Pawlowski et al ( 2021 ) have suggested that an optimization of eDNA analytical method or standardization needs to be developed in order to improve the terrestrial biomonitoring for certain taxa.…”
Section: Introductionmentioning
confidence: 99%